Identification of Novel ErbB3-Interacting Factors Using the Split-Ubiquitin Membrane Yeast Two-Hybrid System - Thaminy, Safia; Auerbach, Daniel; Arnoldo, Anthony; Stagljar, Igor (Genome Research, 2003)
Analysis of membrane protein interactions is difficult because of the hydrophobic nature of these proteins, which often renders conventional biochemical and genetic assays fruitless. This is a substantial problem because proteins that are integral or associated with membranes represent approximately one-third of all proteins in a typical eukaryotic cell. We have shown previously that the modified split-ubiquitin system can be used as a genetic assay for the in vivo detection of interactions between the two characterized yeast transmembrane proteins, Ost1p and Wbp1p. This so-called split-ubiquitin membrane yeast two-hybrid (YTH) system uses the split-ubiquitin approach in which reconstitution of two ubiquitin halves is mediated by a protein–protein interaction. Here we converted the split-ubiquitin membrane YTH system into a generally applicable in vivo screening approach to identify interacting partners of a particular mammalian transmembrane protein. We have demonstrated the effectiveness of this approach by using the mammalian ErbB3 receptor as bait and have identified three previously unknown ErbB3-interacting proteins. In addition, we have confirmed one of the newly found interactions between ErbB3 and the membrane-associated RGS4 protein by coimmunoprecipitating the two proteins from human cells. We expect the split-ubiquitin membrane YTH technology to be valuable for the identification of potential interacting partners of integral membrane proteins from many model organisms.